Difference in brain dynamics during arithmetic task performed in stress and control conditions - Subhani, A.R. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper highlights the difference in brain dynamics in terms of activity and connectivity of the brain between stress and control conditions. In a cross-over experimental design, 22 subjects participated to perform arithmetic task under stress and control environments in which electroencephalogram (EEG) data were recorded. Prior to arithmetic task in both conditions, EEG data were recorded in eyes-open rest condition to be used as baseline. Mean absolute power and coherence of EEG scalp potentials in delta, theta, alpha and beta bands were measured and used as activity and connectivity of the brain. Results show an overall increased activation during stress and control conditions. Between the conditions, the significant difference in power was found in beta band showing difference in parietal region. The coherence maps generally showed hypercoherence in every band between two conditions. © 2016 IEEE.